Predictive Factors of the Survival of Women With Invasive Breast Cancer in French Guiana: The Burden of Health Inequalities - Roué, Tristan; Labbé, Sylvain; Belliardo, Sophie; Plenet, Juliette; Douine, Maylis; Nacher, Mathieu (Clinical breast cancer, 2016)
The aim of this study was to compare the relative survival of patients with invasive breast cancer between women from French Guiana (a French territory in South America) and women from metropolitan France. To our knowledge, no study has compared the survival of breast cancer on the basis of immigrant status in France. Our study underlined that access to care for migrants is challenging, which generates health inequalities. The prognosis of patients with breast cancer in French Guiana is worse than in France, with 23 deaths per 100 incident cases versus 17 per 100 in metropolitan France. This study aimed to compare the relative survival of patients with invasive breast cancer (IBC) between women from French Guiana and metropolitan France and to determine risk factors influencing breast cancer survival in French Guiana. Data were collected from the Cancer Registry of French Guiana. We compared the relative survival of women with IBC between French Guiana and metropolitan France. We used the Cox proportional hazard regression to evaluate the effect of prognostic factors on cancer-specific mortality in French Guiana. We included all 269 cases of IBC in women diagnosed in French Guiana between 2003 and 2009. The overall 5-year relative survival rate of patients with IBC was 79% in French Guiana and 86% in metropolitan France. The place of birth (foreign country vs. French territory), the tumor stage at the time of diagnosis, the mode of diagnosis (symptoms vs. screening), the presence of hormone receptors in the tumor, and the histologic type were the variables associated with survival differences. None of the other study variables were significantly associated with prognosis. Access to care for migrants is challenging, which leads to health inequalities. Early detection through prevention programs is crucial to increase IBC survival, notably for foreign-born patients.